Labyrinth of darkness [1980-1989] - Barta, Jiri (New York : Kimstim, 2006)
DVD includes: Balada o zeleném dřevu = A ballad about green wood (11 min.) ## Klub odloženych = The club of the laid off (25 min.) ## Projekt = The design (6 min.) ## Diskjockey = Disc jockey (10 min.) ## Poslední lup = The last theft (21 min.) ## Hádanky za bonbón = Riddles for a candy (8 min.) ## Krysař = The pied piper of Hamelin (55 min.) ## Zaniklý svět Rukavic = The vanished world of gloves (16 min.).
film
Keywords: Barta, Jiri